Key generation technique based on triangular coordinate extraction for hybrid cubes - Mushtaq, Muhammad Faheem; Jamel, Sapiee; Mohamad, Kamaruddin Malik; Ahmad Khalid, Shamsul Kamal; Mat Deris, Mustafa (Faculty of Electronic and Computer Engineering (FKEKK), Universiti Teknikal Malaysia Melaka (UTeM), 2017)
Cryptographic algorithms play an important role in information security where it ensures the security of data across the network or storage. The generation of Hybrid Cubes (HC) based on permutation and combination of integer numbers are utilized in the construction of encryption and decryption key in the non-binary block cipher. In this study, we extend the hybrid cube encryption algorithm (HiSea) and our earlier Triangular Coordinate Extraction (TCE) technique for HC by increasing the complexity in the mathematical approaches. We proposed a new key generation technique based on TCE for the security of data. In this regard, the Hybrid Cube surface (HCs) is divided into four quarters by the intersection of primary and secondary diagonal and each quarter is rotated by using the rotation points. The overall security of HC is improved by the rotation of HCs and enhanced the complexity in the design of key schedule algorithm. The brute force and entropy test are applied in experimental results which proved that the proposed technique is suitable for implementing a key generation technique and free from any predicted keys pattern.